Transjugular approach for radiofrequency ablation of permanent junctional reciprocal tachycardia in a newborn with bilateral femoral vein thrombosis - Mustafa Gülgün; Tevfik Karagöz; Hakan Hayrettin Aykan; İlker Ertuğrul (KARE Publishing, 2015)
Although radiofrequency ablation is the first line therapy in some children with supraventricular tachycardia, its application in small children is still limited. Herein, we presented a premature newborn diagnosed as multidrugresistant permanent junctional reciprocal tachycardia, and treated by radiofrequency ablation via the jugular vein approach because of bilateral femoral vein thrombosis. We think that when there is limited vascular access, the transjugular route for radiofrequency ablation might be considered as an alternative treatment in newborns with multidrugresistant supraventricular tachycardia.